Sustained censorship in IT (2026-06) (Italy) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Italy. Data sourced from OONI.
Censorship Incident ID: IT-2026-0028. Severity: critical. Confidence: 85%